Actitud hacia la investigación y su importancia en la elección de la modalidad de tesis para optar el título profesional - Mamani Benito, Oscar Javier (2019)
The aim of this review is to highlight the importance of a favorable attitude toward research in the process of elaboration of the university thesis. Attitude is a predisposition to accept or not an object. Its three components such asbeliefs (cognitive), feelings and emotions (affective) and behavioral dispositions or behavior (behavioral), allowedthrough its properties as direction and intensity, show if the attitude is assumed to be positive or negative, as wellas favorable or unfavorable, in this case to the investigation. In that sense the attitude toward scientific research is apredisposition that precedes the process of conducting a thesis, and since the behavior depends on the bias, conducive to a positive attitude that problems are addressed systematically, that the information and ideas critically evaluateit, becoming possible to effectively deal with the process of doing a thesis.